2018
DOI: 10.1371/journal.pone.0202203
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic fluid overload predicts survival and cardiovascular event in incident Chinese peritoneal dialysis patients

Abstract: BackgroundFluid overload is common among asymptomatic peritoneal dialysis (PD) patients. We aim to determine the prevalence and prognostic significance of fluid overload, as measured by bioimpedance spectroscopy, in asymptomatic incident PD patients.MethodsWe performed a single-center study on 311 incident PD patients. Volume status was represented by the volume of overhydration (OH), OH/extracellular water (ECW) ratio, ECW/total body water (TBW) ratio, and ECW to intracellular water (ICW) ratio (E:I ratio). P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 24 publications
2
45
0
1
Order By: Relevance
“…Fluid overload is common in PD patients [37][38][39][40][41][42][43][44] and an independent predictor of all-cause mortality [39,42]. Ng et al [41] reported that fluid overload was common in asymptomatic incident PD patients and a strong predictor of patient survival and cardiovascular events. Moreover, fluid overload was independently associated with decline in RKF in PD patients [45].…”
Section: Discussionmentioning
confidence: 99%
“…Fluid overload is common in PD patients [37][38][39][40][41][42][43][44] and an independent predictor of all-cause mortality [39,42]. Ng et al [41] reported that fluid overload was common in asymptomatic incident PD patients and a strong predictor of patient survival and cardiovascular events. Moreover, fluid overload was independently associated with decline in RKF in PD patients [45].…”
Section: Discussionmentioning
confidence: 99%
“…Body composition and hydration status were assessed by multifrequency bioimpedance spectroscopy (Body Composition Monitor, Fresenius Medical Care, Germany), the method of which was described previously. 23,24 Vascular stiffness was represented by arterial pulse wave velocity (PWV) as measured by an automatic computerized recorder and analyzed using the Complior ® SP program (Artech Medical, France). The method of PWV measurement has been described previously.…”
Section: Assessment Of Nutrition Body Composition and Vascular Stifmentioning
confidence: 99%
“…Überwässerung bei HD-(Hämodialyse) und PD-Patienten (PD: Peritonealdialyse) geht mit einer erhöhten Sterblichkeitsrate einher, und bereits eine symptomlose, klinisch nicht sichtbare Überwässerung ist mit einer schlechteren Herz-Kreislauf bedingten Sterblichkeit assoziiert [1,2]. Vorsichtiger, aber konsequenter Wasserentzug bis zum Erreichen eines Trockengewichts vermindert den Bedarf an Antihypertensiva und verbessert sowohl den Blutdruck, die Herz-Kreislauf-Funktion als auch das Überleben von Dialysepatienten.…”
Section: Warum Ist Die Erkennung Von üBerwässerung Bei Dialysepatientunclassified